Eksistensi Viktimologi dalam Penyelesaian Ganti Rugi - sri suhartati astoto (Jurnal Hukum IUS QUIA IUSTUM, 2001)
Victim those person who are thereatenedor destroyed by an act or ommision of another (man, structure, organization or institusion) and consequently, a punishible act (not only criminal act but also other punishable acts as misdemeanors, economic offeneses, non fuifiiment or work duties) or from an accident (accident at work, at home, traffic accident, etc). Suffering may becaused by anbotherman (man-made victim) not her structure wherepeople are also invoied.